2000
DOI: 10.1002/1521-3757(20000804)112:15<2791::aid-ange2791>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Crystals of Poly(3‐Alkyl‐ thiophene)s: Direct Visualization of Polymer Folds in Submolecular Resolution

Abstract: Die molekularen Parameter von Kopf‐Schwanz‐verknüpften Poly(3‐alkylthiophenen) 1 (R=C6H13, C12H25) wurden rastertunnelmikroskopisch an zweidimensionalen Kristallen bestimmt. Die Polymerfaltungen und ‐konformationen wurden mit submolekularer Auflösung abgebildet (siehe Bild von 1 mit R=C12H25). Darüber hinaus konnte eine elektronische Kopplung zwischen diesen „molekularen Drähten”︁ und denen einer parallel angeordneten zweiten Schicht nachgewiesen werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…[57] The most recent approach grew fibers [57,58] by slow cooling of P3HT solutions, with the crystalline fibers being isolated from the amorphous material by centrifugation and filtration. The fibers were reformulated in dispersions with PCBM, and used for solar-cell processing.…”
Section: Towards a Better Control Of Morphologymentioning
confidence: 99%
“…[57] The most recent approach grew fibers [57,58] by slow cooling of P3HT solutions, with the crystalline fibers being isolated from the amorphous material by centrifugation and filtration. The fibers were reformulated in dispersions with PCBM, and used for solar-cell processing.…”
Section: Towards a Better Control Of Morphologymentioning
confidence: 99%
“…Secondly, the chain folding in conjugated polymers is also different from those in flexible polymers. In conjugated polymers, a more extended chain-folding exists, i.e., seven thiophene rings in the folding section in P3HT and nine for P3DDT ( Figure 5b) [70]. Similar to flexible chains, the chain-folding could drive the crystallization of chains.…”
Section: Structural Differences Between Conjugated Polymers and Fleximentioning
confidence: 99%
“…However, due to the elongated persistence length of chains arising from conjugation plane in backbones, the single chains of conjugated polymers display a more anisotropic extended conformation with less bending like paperclips, compared to the isotropic and disordered coils of more flexible chains (Figure 5a) [69]. Besides, the chain-folding in backbones for conjugated polymers is a more extended one than flexible chains, i.e., seven thiophene rings in the folding section in P3HT and nine for P3DDT (Figure 5b) [70]. The rigid folding results in a severe entanglement of conjugated polymer chains according to the theory reported by Wu et al [134].…”
Section: Equilibrium Between Coil Unimers and Disordered Aggregatesmentioning
confidence: 99%
“…[5][6][7][8][9][10] A number of recent studies have demonstrated that molecular ordering along the polymer backbone and between chains is far more important to carrier transport in high molecular weight (Mw) polymer films than domain boundaries. [11][12][13][14][15][16] However, high Mw semi-flexible polymers are thought to be difficult to push into a highly molecularly ordered state due to entanglements and interactions which can inhibit molecular diffusion and challenge conformational transitions.…”
Section: Introductionmentioning
confidence: 99%